Study on Tooth Profile Parameter of Gear Skiving Under the Influence of Multiple Factor - Zhongliang Qiu; Siming Wang (Jixie chuandong)
Aiming at the tooth profile deviation caused by the shaft angle error during the internal gear skiving， the motion relationship between the tool and the workpiece under the tool feed mode is established. Then， the mathematical models of the tooth profile deviation and tooth profile runout with the rotation speed of the tool and workpiece， the feeding speed of the tool， the helical angle of the tool， the shaft angle and the shaft angle error are established. And the generation mechanism of tooth profile deviation and tooth profile runout under the positive error of shaft angle are analyzed. Finally， on the basis of the mathematical model， the influence of the rotational speed of tool and workpiece， tool feeding speed， helix angle of the tool and shaft angle on tooth profile deviation and tooth profile runtout are analyzed. A certain guidance for the selection of technology in gear skiving is provided.